Fatores prognósticos para o abandono precoce do tratamento da dependência do álcool, crack e outras drogas em uma comunidade terapêutica - Perrone, Pablo Andrés Kurlander [UNESP] (2014)
The present paper aims investigate the different factors that can be prognostics to time of permanence of alcohol and drugs dependents in treatment on a Therapeutic Community, as well as to dropout, considering that time of treatment lower than three months and dropout are prognostic factors to relapse. For this longitudinal study was conducted in a group of alcohol and drugs dependents in treatment on a Therapeutic Community, to evaluate the so-ciodemographic characteristics, severity of dependence and the presence of anxiety and de-pression at start of treatment. The treatment outcome was assessed using a continuous varia-ble (time of permanence - days) and a categorized (dropout - conclusion). The different fac-tors that can be associated to this two variables have been assessed, univariate and multivar-iate form, aiming better comprehension what collaborates with early dropout (less than 90 days of permanence) and, consequently, to recurrence. The survey had 91 subjects, of whom 67 (74.0%) dropped out of treatment, with 45 (67.0%) cases of early dropout. The main age ranges were 25-35 years old (38.5%) and 36-50 years old (29.7%). Regarding other socio-demographic data, 41.7% were single, 72.5% with low education level, 36.3% were working before admission, 65.0% middle class, 54.9% white, 44.0% evangelical/protestant and 41.7% catholic. The main drug of abuse was crack (60.4%), followed by alcohol (33.0%). 41.8% reported time of use between 11 to 20 years, 75.8% were smokers, 30.8% used psychoactive medication at entering in treatment and 67.0% reported alcohol and other drugs dependents in the family of cohabitation. 52.7% had other admissions in Therapeutic Community, 19.8% have been in the same Therapeutic Community of this study and 38.5% had been arrested. Regarding the presence of anxiety and depression at the beginning of treatment, low levels have been found, being the probable score on 19.0% for anxiety and 7.0% for ...